Ecotoxicological impact of DON toxin on maize (Zea mays L.) germination - Gálya, Bernadett; Nagy, Attila; Bíró, Györgyi; Mézes, Lili; Borbély, János; Tamás, János (Acta Agraria Debreceniensis, 2014)
Fusarium graminearum is one of the most significant arable pathogen in Hungary, and various types of trichothecene mycotoxins (mostly DON, deoxynivalenol) are detected most commonly in cereals (Biró et al., 2011). Fusarium infection and mycotoxin production could not be eliminated, and infected maize by Fusarium sp. cannot be exploited as food, seed, or animal feed. However it can be raw material of biogas production. In this research we would like to investigate the content and effect of the toxin in the end product of biogas production on plant germination. The Fusarium sp. can cause mildew and seedling mortality in seed of maize (Zea mays L.), so we examine the effect of this on germination. In preliminary examination Fusarium sp. was not detected in the bioreactor of the Institute after the retention time (30 day), however it can be assumed that during the hydrolysis of the fungus growth and mycotoxin production also increased exponentially. There were no appropriate tools to detect the toxin in the end product of biogas production so modelling of anaerobic hydrolysis was necessary. The effects of hydrolyzed product for germination were also detected.